A low power wideband RGC-based modified-MIC trans-impedance amplifier in 0.18 ​μm CMOS process. (February 2020) - Hosseini, Maryam; Jafarnejad, Roya; Sobhi, Jafar; Koozehkanani, Ziaaddin Daie
Abstract: This paper presents a novel Trans-Impedance Amplifier (TIA) based on Regulated-Cascode (RGC) structure. A modified MOS-based Immittance Converter (MIC) is used to achieve high bandwidth with lower power consumption. Combining the MIC scheme with RGC structure, in the presence of an inductor, provides both a negative input resistance which increases the input pole frequency and a negative inductance which improves stability of the circuit. As a result, -3 ​dB bandwidth enhances while consuming lower power. Post-layout simulation results in TSMC 0.18 ​μm CMOS technology show a trans-impedance gain of 49.7 ​dB with -3dB bandwidth of 9.2 ​GHz considering 500 ​fF of photodiode capacitance at the TIA input. The circuit occupies an active area of 0.068 ​mm 2 and consumes 5.3 ​mW from a 1.8-V supply. The minimum input-referred current noise of the TIA is about 15.3 pA/√Hz.